Developmental State or Developmental Market? The Cameron-Clegg Government’s Response to the Financial Crisis - Simon Lee (Revue Française de Civilisation Britannique)
The policies and actions of the Cameron-Clegg government, and its successor single party Conservative government led by David Cameron since its victory at the 7 May 2015 General Election, should not be seen in isolation. Since May 1979, successive United Kingdom governments have claimed to be restoring an entrepreneur-led enterprise culture, based upon a ‘developmental market’ political rhetoric and agenda. However, this article argues that successive United Kingdom governments from Thatcher to Cameron have in fact reflected a developmental state tradition which can be traced back to England’s financial revolution during the seventeenth century. Where late industrializing economies have pursued a developmental state strategy based upon the nurturing of competitive advantage in civilian manufacturing industries, England (and latterly the United Kingdom) has pursued a developmental state strategy founded upon competitive advantage in financial markets and military industries. It is this developmental state tradition which can account for the British state’s provision of a £1.162 trillion bailout of United Kingdom banks, and the fiscal austerity implemented since May 2010. Rather than having been shaped by a developmental market, as the basis for a Hayekian constitution of liberty, the United Kingdom’s government’s response to the 2007-2008 financial crisis has witnessed not a rolling back but a wholesale redefinition of the role of the British state through the passage of laws and legislation designed to defend the interests and deal with the consequences of the exercise of arbitrary market power. In this sense, in the words of Philip Mirowski, the United Kingdom government has not let the 2008 crisis go to waste.